(untitled) - Mead, Margaret (New York, 1963)
The mountain-dwelling arapesh, The river-dwelling mundugumor, The lake-dwelling tchambuli, the implication of these results
Keywords: Dân tộc học,Ethnology; Papua New Guinea,Papua New Guinea